Molecular characterization of novel mitochondrial peroxiredoxins from the Antarctic emerald rockcod and their gene expression in response to environmental warming - Tolomeo, A. M.; Carraro, A.; Bakiu, R.; Toppo, S.; Garofalo, F.; Pellegrino, D.; Gerdol, M.; Ferro, D.; Place, S. P.; Santovito, G. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2019)
In the present study we describe the molecular characterization of the two paralogous mitochondrial peroxiredoxins from Trematomus bernacchii, a teleost that plays a pivotal role in the Antarctic food chain. The two putative amino acid sequences were compared with orthologs from other fish, highlighting a high percentage of identity and similarity with the respective variant, in particular for the residues that are essential for the characteristic peroxidase activity of these enzymes. The temporal expression of Prdx3 and Prdx5 mRNAs in response to short-term thermal stress showed a general upregulation of prdx3, suggesting that this isoform is the most affected by temperature increase. These data, together with the peculiar differences between the molecular structures of the two mitochondrial Prdxs in T. bernacchii as well as in the tropical species Stegastes partitus, suggest an adaptation that allowed these poikilothermic aquatic vertebrates to colonize very different environments, characterized by different temperature ranges.